Problem-solving skills and hardiness as protective factors against stress in Iranian nurses - Abdollahi, Abbas; Abu Talib, Mansor; Yaacob, Siti Nor; Ismail, Zanariah (Taylor & Francis, 2014)
Nursing is a stressful occupation, even when compared with other health professions; therefore, it is necessary to advance our knowledge about the protective factors that can help reduce stress among nurses. The present study sought to investigate the associations among problem-solving skills and hardiness with perceived stress in nurses. The participants, 252 nurses from six private hospitals in Tehran, completed the Personal Views Survey, the Perceived Stress Scale, and the Problem-Solving Inventory. Structural Equation Modeling (SEM) was used to analyse the data and answer the research hypotheses. As expected, greater hardiness was associated with low levels of perceived stress, and nurses low in perceived stress were more likely to be considered approachable, have a style that relied on their own sense of internal personal control, and demonstrate effective problem-solving confidence. These findings reinforce the importance of hardiness and problem-solving skills as protective factors against perceived stress among nurses, and could be important in training future nurses so that hardiness ability and problem-solving skills can be imparted, allowing nurses to have more ability to control their perceived stress.